MODU MODU: a multifunctional and zero waste collection - Fang, Hanyun (Nanyang Technological University, 2022)
I have always wondered: if my clothes could transform – I can wear something appropriate for family dinners/work, and still look good when I meet my friends for drinks/fancy meals after wards, without having to choose between going home to change out and looking boring for the fun night. This was merely a thought and fantasy of mine until recently, after I researched about the effects of fast fashion and overconsumption on our environment, and how we, as designers could change the way we design to play our part. Combined with my thoughts of creating multifunctional pieces, that was what pushed me to go ahead with creating this project. This report explores the research, process, production, branding of the final modular collection that is multi-functional and zero waste.